Relationship Between Duration of Exclusive Breastfeeding and Cognitive Development in Children: A Systematic Study - Ruth Olivia Widianto; Johannes Cancius Prihadi; Ellen Wijaya; Laurentius Aswin (Eduvest - Journal of Universal Studies, 2025)
Cognitive development is a crucial aspect of a child's overall growth. This process refers to the stages in which the child undergoes changes that help them remember, understand, process information, and solve problems. One of the key factors in enhancing cognitive development in children is exclusive breastfeeding, defined as breastfeeding without any complementary foods since birth. This systematic review aims to determine the optimal duration of exclusive breastfeeding for cognitive development in children. This research is a systematic review focusing on journals published between 2012 and 2022, using the keywords ("duration" OR "month" OR "months") AND ("exclusive breastfeeding" OR "exclusive breastmilk feeding") AND ("cognitive development" OR "intelligence quotient" OR "cognitive abilities") in the PubMed, ScienceDirect, and ProQuest databases. The review was conducted based on the PRISMA guidelines and evaluated using the JBI Critical Appraisal tools. The results identified three relevant journals. Research by Jedrychowski et al. (2012) and Cando reported that exclusive breastfeeding for six months led to greater cognitive development improvements in children compared to durations of less than six months. In contrast, Choi et al. (2018) found that exclusive breastfeeding for less than six months resulted in higher cognitive development gains compared to six months. This systematic review indicates a relationship between exclusive breastfeeding and improvements in cognitive development in children. This association is likely attributed to the nutrients found in mother's milk, such as omega-3, which are beneficial for supporting children's cognitive development.